Undergraduate students' perceptions of learning about leadership in multifaith workplace. Issue 5 (19th October 2020) - Allen, Stuart; Williams, Peter; Crowson, Howard Michael
ABSTRACT: Workplace demographic changes and evidence of religious discrimination suggest that management educators should prepare students for multi-faith workplaces. However, quantitative research is lacking on the impact of courses designed to prepare students for multifaith workplaces or organizations where spirituality is expressed. This quasi-experimental study examined the effects of a two-hour online lesson on leadership, religion, and spirituality on undergraduate students' perceptions of the topic in pre-, post-, and eight-week post-lesson surveys. Two factors emerged representing students' perceptions. Changes in interest and openness to learning about leadership, religion, and spirituality were sustained over eight weeks. Changes in fear or apprehension about engaging this topic in the classroom or workplace were transient, decreasing initially, but returning to pre-lesson levels at eight weeks. This study's findings suggest that a single lesson shows potential to increase students' openness and interest in learning about the intersection of leadership, religion, and spirituality.